Cadaver imprint on soil chemistry and microbes - Knowns, unknowns, and perspectives - Fiedler, Sabine; Kaiser, Klaus; Fournier, Bertrand (Frontiers in Soil Science, 2023)
Cadaver-decomposition unleashes an ephemeral pulse of matter input that modifies microbial communities, as well as nutrient pools and fluxes. This leaves behind a measurable imprint on affected soils. However, the persistence of this imprint remains poorly understood. We define cadaver imprint persistence as the entire period between time of cadaver deposition and time when cadaver effects on microbial community structure and chemical indicators are no longer detectable. We present a brief overview of published results on the cadaver-induced changes in the bio-elements carbon, nitrogen and phosphorus, which regulate the structure and functions of the soil microbiome. Based on this, we identified conceptual and methodological gaps and biases and suggest potential research avenues to address them. This will help to better understand the relationships between cadaver-derived matter and microbial taxa and functions, as well as the role of cadaver-decomposition within and across ecosystems. The proposed future research on cadaver-derived imprint on soils has the potential to serve as a hub for connecting soil chemistry, microbial ecology, forensic sciences, and ecosystems science.